Evaluation of Extremity Tissue and Bone Injury after Intraosseous Hypertonic Saline Infusion in Proximal Tibia and Proximal Humerus in Adult Swine. (2nd October 2014) - Bebarta, Vikhyat S.; Vargas, Toni E.; Castaneda, Maria; Boudreau, Susan
Abstract Background. Hypertonic saline (HTS) has been reported as a treatment for sever traumatic brain injury and hemorrhagic shock and current clinical guidelines recommend it. Intraosseous (IO) infusion is often needed in the pre-hospital and combat settings to administer life-saving treatments. However, the safety of IO HTS infusion is not clear. The aim of our study was to evaluate the clinical and histological outcome of HTS IO infusion into the extremity of a large animal model. Methods. We conducted a randomized comparative study of adult pigs that were infused intraosseously with one of the following solutions: 7.5% HTS, 3% HTS or normal 0.9% isotonic saline. The animals were observed daily for infection, necrosis and gait (5 point Tarlov score) up to 5 days. Five days after infusion, necropsy and histological analysis was performed using a validated scale of tissue necrosis. Results. The mean Tarlov gait scores were similar in all arms and all animals showed a score of 4 (normal ambulation) by day 5. During the 5 day observation period, there were no signs of infection or tissue abnormalities. Histological examinations showed no indication of necrosis, or abnormal bone and muscle healing (p < 0.05). Conclusion. We observed regular tissue morphology and normal gait scores over the 5 day observation period. There was an absence of gross tissue necrosis and microscopic ischemia post IO HTS infusion in this swine model. This data confirms the clinical safety of IO HTS infusion and highlights its use as an alternative lifesaving treatment.